Health personnel education in South Africa - Rachael V Gumbi; Marie E Muller (AOSIS, 1996)
The education of South African health personnel should be reality-based and therefore focused on the real needs of the country. Opsomming Die opleiding van Suid-Afrikaanse gesondheidspersoneel behoort op die realiteit gebaseer te word en derhalwe op die behoeftes van die land. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.